Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1163/22941932-90000064
|View full text |Cite
|
Sign up to set email alerts
|

Seed provenance influences the wood structure of Gallesia Integrifolia

Abstract: Plants from three provenances of Gallesia integrifolia were cultivated under homogeneous growth conditions to determine the effect of seed provenance on the wood density, anatomy and chemical constituents. In 1981, seeds were collected in Ribeirão Preto (RP), Campinas (CA) and Bauru (BA). Seedlings of the three provenances were planted at the Luiz Antonio Station in 1982 and trees were felled in 2008. The plants showed significant differences in their wood, possibly due to different genotypes. The relatively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…This result was also verified by regression (linear) analysis (Figure 7a-b). We observed the same pattern with two other native Brazilian trees, Cariniana legalis (Lima et al, 2011) and Gallesia integrifolia (Longui et al, 2011). Similar results were found for many species (Gartner, 1995;Baas et al, 2004).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This result was also verified by regression (linear) analysis (Figure 7a-b). We observed the same pattern with two other native Brazilian trees, Cariniana legalis (Lima et al, 2011) and Gallesia integrifolia (Longui et al, 2011). Similar results were found for many species (Gartner, 1995;Baas et al, 2004).…”
Section: Resultssupporting
confidence: 88%
“…The variation in density toward the bark is also quite common in Brazilian native woods, and we have observed this phenomenon in all of our studies (Lima et al, 2011a;Lima et al, 2011b;Longui et al, 2011). Hietz et al (2013) reported hundreds of species in Panamanian and Ecuadorian forests and noted that the wood density was negatively related to tree growth and mortality and that wood density tended to increase towards the bark on trees with low initial density and decrease in the direction of the bark on trees with high initial density.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…For the vessel diameter, similar values were found. The radial association observed between increased vessel diameter and the concomitant reduction in the frequency has been described for hardwoods (Longui et al 2011, Naji et al 2013. For this present study we found that this effect was more pronounced in the vicinity of the pith, which may be related to the initial rapid tree-height growth, characteristic of pioneer species, since the vessel elements are strongly influenced by the decreasing auxin concentration gradient along the axial axis of the tree, where the wood produced far from the young leaves, which with the growth in stem diameter comprises the near-pith region, and produced in the opposite direction to the transport of water, tends to present larger and less frequent vessels (Aloni and Zimmermann 1983, Aloni 2013, Sorce et al 2013.…”
Section: Effect Of Radial Positionmentioning
confidence: 76%